Cu/SAPO-34 prepared by a facile ball milling method for enhanced catalytic performance in the selective catalytic reduction of NOx with NH3. Issue 39 (1st October 2019) - Chang, Huazhen; Qin, Xuan; Ma, Lei; Zhang, Tao; Li, Junhua
Abstract : Cu/SAPO-34 catalysts were prepared by different solid-state ion exchange methods, i.e., mechanical mixing (Cu/SAPO-34-M) and ball milling (Cu/SAPO-34-B), and were used for selective catalytic reduction of NO x with NH3 (NH3 -SCR) reaction. Abstract : Cu/SAPO-34 catalysts were prepared by different solid-state ion exchange methods, i.e., mechanical mixing (Cu/SAPO-34-M) and ball milling (Cu/SAPO-34-B), and were used for selective catalytic reduction of NO x with NH3 (NH3 -SCR) reaction. Compared with Cu/SAPO-34-M, Cu/SAPO-34-B exhibited more excellent NH3 -SCR catalytic activity. Various characterization methods, including XRD, SEM, N2 adsorption–desorption, UV-vis, H2 -TPR, EPR, NO + O2 -TPD, NH3 -TPD, and in situ DRIFTS, were used to elucidate their different catalytic performances. The characterization results suggested that ball milling could be beneficial for increasing the amount of isolated Cu 2+ ions in the Cu/SAPO-34 catalyst. In comparison with Cu/SAPO-34-M, Cu/SAPO-34-B had more isolated Cu 2+ ions, which mainly contributed to the NO x adsorption and Lewis acid sites. Furthermore, ball milling could improve the redox property of the Cu/SAPO-34 catalyst. The in situ DRIFTS results verified that NH3 adsorbed on Lewis acid sites were more active than those adsorbed on Brønsted acid sites. Therefore, it was believed that ball milling was a suitable method to prepare more efficient Cu/SAPO-34 catalysts for NO x removal from diesel exhaust.